Internal self-determination in international law history, theory, and practice - Senaratne, Kalana 1983- (Cambridge University Press, 2021)
Internal self-determination is an under-explored topic in international law. It is popularly understood to be a principle of relatively recent origin, promoting democratic freedoms to populations and autonomy for minority groups within states. It has also been viewed as a principle receiving the support of Western states, in particular. In this first book-length critical study of the topic, the reader is invited to rethink the history, theory and practice of internal self-determination in a complex world. Kalana Senaratne shows that it is a principle of great, but varied, potential. Internal self-determination promises democratic freedoms and autonomy to peoples; but it also represents an idea which is not historically new, and is ultimately a principle which can be promoted for different and conflicting purposes. Written in a clear and accessible style, this book will be of interest to international lawyers, state-officials, minority groups, and students of law and politics